(-3/7+5/11):(-3/5)+(-4/7+6/11):(-3/5)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
b: \(27D=3^{14}+3^{17}+...+3^{2024}\)
\(\Leftrightarrow26D=3^{2024}-3^{11}\)
hay \(D=\dfrac{3^{2024}-3^{11}}{26}\)
c: \(25E=-5^4-5^6-...-5^{1002}\)
\(\Leftrightarrow24E=-5^{1002}+5^2\)
hay \(E=\dfrac{-5^{1002}+5^2}{24}\)
d)\(\frac{2}{3.5}+\frac{2}{5.7}+....+\frac{2}{97.99}\)
\(=\frac{1}{3}-\frac{1}{5}+\frac{1}{5}-\frac{1}{7}+....+\frac{1}{97}-\frac{1}{99}\)
\(=\frac{1}{3}-\frac{1}{99}\)
\(=\frac{32}{99}\)
a) 11/4x(-0,4)x-1,6x11/4
= -1,1 x-1,6x11/4
= 1,76x11/4
= 4,48
b) 6/19x-7/11+6/19x-4/19x-4/11+13/19
= -42/209+96/3971+13/19
= -702/3971+13/19
= 2015/3971
c) 2/5x3/7+-3/7x3/5+3/7
= 3/7x(2/5+3/5+1)
= 3/7x(1+1)
= 3/7x2
= 6/7
d) 2/3x5+2x5/7+2/7x9+....+2/97x99
= 1/3-1/5+1/5-1/7+1/7-1/9+......+1/97-1/99
= 1/3-1/99
= 32/99
Bài 1:
a: \(x=\dfrac{2}{3}:\dfrac{3}{5}=\dfrac{2}{3}\cdot\dfrac{5}{3}=\dfrac{10}{9}\)
b: \(x=\dfrac{17}{8}:\dfrac{7}{17}=\dfrac{17}{8}\cdot\dfrac{17}{7}=\dfrac{289}{56}\)
c: \(x=-\dfrac{3}{4}:\dfrac{7}{12}=\dfrac{-3}{4}\cdot\dfrac{12}{7}=\dfrac{-63}{28}=-\dfrac{9}{4}\)
d: \(\Leftrightarrow x\cdot\dfrac{1}{6}=\dfrac{3}{8}-\dfrac{1}{4}=\dfrac{1}{4}\)
hay \(x=\dfrac{1}{4}:\dfrac{1}{6}=\dfrac{3}{2}\)
e: \(\Leftrightarrow\dfrac{1}{2}:x=-4-\dfrac{1}{3}=-\dfrac{17}{3}\)
hay \(x=-\dfrac{1}{2}:\dfrac{17}{3}=\dfrac{-3}{34}\)
1: =72/90+65/90=137/90
2: =24/56-77/56=-53/56
3: =-7/10+4/5=1/10
4: =15/100-4/100=11/100
5: =4/6-5/6=-1/6
6: =10/40-15/40-76/40=-81/40
7: =-9/10+7/18
=-81/90+35/90=-46/90=-23/45
8: =27/90-55/90=-28/90=-14/45
9: =36/60-50/60-35/60=-49/60
10: =-4/9+5/6-3/8
=-32/72+60/72-27/72
=1/72
a) \(\frac{7}{2}-\frac{14}{3}+\left(\frac{3}{4}-\frac{7}{3}\right)-\left(\frac{5}{6}-\frac{7}{4}\right)+\frac{11}{2}-3\)
\(=\frac{7}{2}-\frac{14}{3}+\frac{3}{4}-\frac{7}{3}-\frac{5}{6}+\frac{7}{4}+\frac{11}{2}-3\)
\(=\left(\frac{7}{2}+\frac{11}{2}\right)-\left(\frac{14}{3}+\frac{7}{3}\right)-3+\left(\frac{3}{4}+\frac{7}{4}\right)-\frac{5}{6}\)
\(=9-7-3+(\frac{5}{2}-\frac{5}{6})\)
\(=-1+\frac{5}{3}\)
\(=\frac{2}{3}\)
b) \(\frac{7}{3}-\frac{7}{5}+\frac{11}{10}-\left(\frac{2}{5}-\frac{5}{6}\right)+\frac{4}{15}-\frac{4}{3}\)
\(=\left(\frac{7}{3}-\frac{4}{3}\right)-\left(\frac{7}{5}+\frac{2}{5}\right)+(\frac{11}{10}+\frac{5}{6}+\frac{4}{15})\)
\(=1-\frac{9}{5}+\frac{11}{5}\)
\(=1-\left(\frac{9}{5}-\frac{11}{5}\right)\)
\(=1-\left(\frac{-2}{5}\right)\)
\(=1\frac{2}{5}\)
......................?
mik ko biết
mong bn thông cảm
nha ................
`4/7+4`
`=4/7+4/1`
`=4/7+28/7`
`=32/7`
__
`3+6/11`
`=33/11+6/11`
`=39/11`
__
`3-5/7`
`=3/1-5/7`
`=21/7-5/7`
`=16/7`
__
`21/9-2`
`=21/9-18/9`
`=3/9`
`=1/3`
__
`15/24+2`
`=15/24+48/24`
`=63/24`
`=21/16`
__
`63/45-20/25`
`=63/45-4/5`
`=63/45-36/45`
`=27/45`
`=9/15`
__
`3/4-2/8`
`=3/4-1/4`
`=2/4`
__
`6/7-5/8`
`=48/56-35/56`
`=13/56`
__
`37/45-5/9`
`=37/45-25/45`
`=12/45`
`=4/15`
__
`46/39-11/13`
`=46/39-33/39`
`=13/39`
`=1/2`
__
`5/12+3/4+1/3`
`=5/12+9/12+4/12`
`=14/12+4/12`
`=18/12`
`=3/2`
__
`1/2+3/7+11/14`
`=7/14+6/14+11/14`
`=13/14+11/14`
`=24/14`
`=12/7`
__
`7/10-(1/5+1/4)`
`=7/10-(4/20+5/20)`
`=7/10-9/20`
`=14/20-9/20`
`=5/20`
`=1/4`
__
`15/4-2/3-3/4`
`=(15/4-3/4)-2/3`
`=12/4-2/3`
`=3-2/3`
`=9/3-2/3`
`=7/3`
a: =-5/11-6/11+1=-11/11+1=0
b: =-13/17-13/21-4/17=-1-13/21=-34/21
b: \(=-\dfrac{5}{12}\cdot\dfrac{9}{20}\cdot\dfrac{7}{17}=\dfrac{-21}{272}\)
d: \(=\dfrac{13}{17}\left(-\dfrac{4}{5}-\dfrac{3}{4}\right)=\dfrac{13}{17}\cdot\dfrac{-31}{20}=\dfrac{-403}{340}\)
a) 5/9 + 4/9 . 3/7 + 4/9 . 4/7
= 5/9 + 4/9 . (3/7 + 4/7)
= 5/9 + 4/9 . 1
= 5/9 + 4/9
= 1
toán lớp mấy zậy
\(\left(-\frac{3}{7}+\frac{5}{11}\right):\left(-\frac{3}{5}\right)+\left(\frac{-4}{7}+\frac{6}{11}\right):\frac{3}{5}\)
\(=\left(-\frac{3}{7}+\frac{5}{11}\right).\left(-\frac{5}{3}\right)+\left(-\frac{4}{7}+\frac{6}{11}\right).\left(-\frac{5}{3}\right)\)
\(=\left(-\frac{3}{7}+\frac{5}{11}-\frac{4}{7}+\frac{6}{11}\right).\left(-\frac{5}{3}\right)\)
\(=\left(-1+1\right).\left(-\frac{5}{3}\right)\)
\(=0.\left(-\frac{5}{3}\right)=0\)